The Epistemological Transformation of Bahtsul Masail in Addressing Women's Economic Rights: From Classical Fiqh Authority to the Maqashid Syariah Approach - Imam Syarbini; Asmawi; Kojin (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction:This study examines the epistemological transformation of Bahtsul Masail in responding to contemporary gender and equality issues within Muslim societies. It aims to explore how the traditional pesantren-based legal deliberation mechanism shifts from a predominantly textual and fiqh-oriented approach toward a maqashid al-shariah-based framework that is more responsive to contemporary social realities. Design/methods/approach – This research employs a qualitative library research method. Data were collected from classical and contemporary fiqh literature, documented Bahtsul Masail decisions, and scholarly works on gender studies, Islamic law, and maqashid al-shariah. The data were analyzed using a descriptive-analytical approach to identify patterns of epistemological change in Islamic legal reasoning. Findings – The study reveals three major transformations in the epistemology of Bahtsul Masail: (1) the expansion of legal reasoning sources beyond classical fiqh texts, (2) the incorporation of multidisciplinary perspectives, including social and gender studies, and (3) the strengthening of maqashid-based principles such as justice (al-‘adl), public welfare (maslahah), and human dignity (karamah al-insan). These developments enable more contextual and adaptive legal responses to contemporary gender-related issues while maintaining Islamic normative foundations. Research implications/limitations – The study is limited to textual and documentary sources and does not examine the practical implementation of Bahtsul Masail decisions in pesantren communities. Future empirical studies are needed to assess their social impact and effectiveness. Originality/value – This study offers a novel perspective by conceptualizing the transformation of Bahtsul Masail as an epistemological shift toward maqashid-oriented legal reasoning. It contributes to the discourse on Islamic legal reform and demonstrates the potential of pesantren institutions to address contemporary challenges related to gender and equality.